2021
DOI: 10.1111/apel.12316
|View full text |Cite
|
Sign up to set email alerts
|

The non‐linearity between finance and economic growth: a literature review and evidence from China

Abstract: The influence of finance on the economy has been shown to be non-linear. When financial development exceeds the needs of the real sector, an economy will face the challenge of 'too much finance', which may generate problems such as rent-seeking, asset price bubbles, or even financial crises. China seems to have followed the 'too much finance' pattern in the most recent decade, during which a fast-expanding financial sector and a slowly growing economy coexisted. The empirical part of this study supports a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Nevertheless, it appears that the evidence as a whole indicates that stock market development is comparatively more favourable for economic growth, particularly for high-income countries, than banking development. In contrast, the beneficial effects of bank development are limited to low-income countries and environments characterized by a modest level of financial development, a finding that is compatible with the recent literature showing the detrimental consequences of 'too much finance (credit)' (Arcand et al, 2015;Xu & Gui, 2021).…”
Section: Of 16supporting
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, it appears that the evidence as a whole indicates that stock market development is comparatively more favourable for economic growth, particularly for high-income countries, than banking development. In contrast, the beneficial effects of bank development are limited to low-income countries and environments characterized by a modest level of financial development, a finding that is compatible with the recent literature showing the detrimental consequences of 'too much finance (credit)' (Arcand et al, 2015;Xu & Gui, 2021).…”
Section: Of 16supporting
confidence: 83%
“…Exploring the relationship between financial structure and economic growth is not only academically meaningful but also policy‐relevant. As the recent literature has shown, excessive financial development, particularly excessive credit expansion, may not only damage economic growth (Arcand et al, 2015; Xu & Gui, 2021) but also lead to serious economic and social problems, such as inequality, banking crises and political instability (Bazillier & Hericourt, 2017; Funke et al, 2016; Kauko, 2014). Policy‐makers may, therefore, be forced to consider curbing banking development to a certain extent and instead promoting the development of financial markets as an alternate means to finance the economy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that it may lead to over-indebtedness for micro-borrowers with low returns on investments, in case of using loans for non-productive sources; this is particularly true for borrowers with low financial literacy (Schicks, 2014). Other studies find a nonlinear relationship between finance and growth (Arcand et al, 2015;Beck et al, 2014;Panizza, 2018;Xu & Gui, 2021). 3 The CGAP is a global partnership of more than 30 leading development organisations that works to advance the lives of poor people through financial inclusion.…”
Section: Importance Of Financial Inclusionmentioning
confidence: 99%
“…However, it seems that there is a paradigm shift in the aftermath of the 2008 financial crisis. As generalized by Xu and Gui (2021, p. 6), “the new generation of finance-growth literature forcefully challenges the conventional wisdom that finance unconditionally, linearly, and monotonically contributes to or even causes economic growth. The finance-growth nexus is now shown to be nonlinear, nonmonotonic, and context dependent.”…”
Section: Banking Development and Economic Growth: Quantity Dimensionmentioning
confidence: 99%